Functional Tests and Surveys Used to Assess Nervous System Dysfunction in Patients with Fabry Disease – A Review - Jesionek, Stanislaw; Parys, Jakub; Mikosińska, Agnieszka; Kaźmierczak, Martyna; Kałuziak, Partycja; Jajczak, Marta; Mossakowski, Maciej; Witek, Aleksandra; Litwin, Mateusz; Jankowska, Justyna (Quality in Sport, 2025)
Introduction and Purpose: Fabry disease (FD) is a rare, X-linked lysosomal storage disorder caused by a deficiency of the enzyme alpha-galactosidase A, leading to progressive multi-organ damage. Among the various complications, autonomic nervous system dysfunction has been suggested as a significant aspect of the disease’s pathophysiology. This review aims to evaluate functional tests and surveys used to assess nervous system dysfunction, focusing on the autonomic nervous system in FD patients. State of Knowledge: Fabry disease presents with classical and non-classical phenotypes, with early symptoms in males often involving pain, skin lesions, and gastrointestinal disturbances, progressing to more severe manifestations like heart failure and renal disease. The autonomic nervous system, which regulates various physiological processes, may be impaired in Fabry patients, potentially contributing to the disease’s symptoms. Functional tests such are frequently used to assess autonomic function. Studies on autonomic dysfunction in FD have provided mixed results, challenging the assumption that autonomic neuropathy plays a central role in disease progression. Methods: A comprehensive search of references related to FDe and the autonomic nervous system was conducted on PubMed using the following search terms: “Fabry disease, autonomic nervous system, blood pressure, cold pressor test, vascular manifestations.” Conclusions: The findings of this review suggest that while autonomic dysfunction may be present in certain subsets of FD patients. Functional tests revealed limited evidence of widespread autonomic dysfunction. QSART showed reduced sweating responses in pain patients but no differences in non-pain patients. These results challenge the widely accepted notion that autonomic neuropathy is a major contributor to Fabry disease symptoms and emphasize the need for further research into the specific mechanisms underlying the disease's clinical manifestations.